SINOVAC VACCINE POLEMIC DISINFORMATION IN ASYMMETRICAL WARFARE PERSPECTIVE - Belinda, Fera; Puspitasari, Maria (UI Scholars Hub, 2021)
The polemic of the China produced Sinovac Vaccine issue spreading among the public, is a form of disinformation used by political opposition to the government, to block and mess up the government’s effort to accelerate handling of Covid-19 transmission in Indonesia. The polemic results in 4 situations, namely; first, decreasing public trust in the government's commitment in eradicating the Covid-19 pandemic. Second, low level of support from the public of the Covid-19 handling programs. Third, delayed and slow economic recovery which brings down the public's economic ability due to increasing number of layoffs caused by decreases in companies’ turnover and affecting the public’s purchasing power. Fourth, the national security aspect, especially on the potential aspect regarding disintegration of the nation. Purpose of this research is to reveal the disinformation via China-made Sinovac vaccine polemic. The research applies disinformation and asymmetric warfare concepts to prove the Sinovac vaccine polemic, while also using a qualitative research approach by making the polemic issue as the object of case study. Data collection technique is done by text observation on social media which covers the Sinovac vaccine polemic. The research discovers that the disinformation effort to the Sinovac vaccine issue is a polemic to the government, that the public assess as slow in handling the spread of Covid-19.